(3aQGFO GdOQQ hahGFO GdacQ aj TQM oeNJUQ GdSjQI dEHf aGQSs - (3CHh Ydj MSf Hf CHj GdbGSe Hf MSf Hf HGOjS GdbSfWjfjs
(3ChdgG (B:s
(3hjHOC CKfGA hUa fbT NGJe GdQShd Udi Gddg Ydjg hSde hGdNdaGA GdCQHYI s
(3BNQgG (B:s
(3hBNQI eHJhQ CjVkG , hBNQ eGajg CKfGA GdJYQja HeUfa GdSjQI (B: (3EHf aGQS s
(3eNJUQ GdSjQI GdfHhjI dCMeO Hf aGQS GdbRhjfj J SfI (B395 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B270s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B308 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs